Two Cases of Acute Macular Neuroretinopathy Associated with the Adenovirus-based COVID-19 Vaccine Vaxzevria (Astrazeneca). (4th July 2022) - Franchi, Alexander; Rauchegger, Teresa; Palme, Christoph; Frede, Katharina; Haas, Gertrud; Blatsios, Georgios; Kralinger, Martina; Zehetner, Claus
ABSTRACT: Purpose: To report two cases of acute macular neuroretinopathy (AMN) in young female patients following the administration of the adenovirus-based coronavirus disease 2019 (COVID-19) vaccine Vaxzevria (AstraZeneca). Methods: Spectral-domain optical coherence tomography and infrared imaging were used to confirm the diagnosis of AMN. Results: Both patients showed a parafoveal hyperreflective band in the outer nuclear layer, disruption of the ellipsoid and interdigitation zones of the photoreceptor layers, and correlating hyporeflective areas on the near-infrared images. Both patients presented with flu-like fever and sudden onset of fortifications within 48 hours of vaccination. One patient showed altered flow in the deep capillary plexus and highly elevated thrombotic parameters. Conclusion: We report a possible association between immune-mediated AMN and the administration of adenovirus-based COVID-19 vaccine Vaxzevria.